Women under Nazi persecution : a primary source supplement based on documents from the International Tracing Service - Jack, Joseph and Morton Mandel Center for Advanced Holocaust Studies; International Tracing Service; Wiener Library (2017)
A project of the United States Holocaust Memorial Museum, Jack, Joseph and Morton Mandel Center for Advanced Holocaust Studies, the International Tracing Service, and the Wiener Library for the Study of the Holocaust & Genocide